Rapid drug susceptibility testing with a molecular beacon assay is associated with earlier diagnosis and treatment of multidrug-resistant tuberculosis in California - Banerjee, Ritu; Allen, Jennifer; Lin, S-Y Grace; Westenhouse, Janice; Desmond, Ed; Schecter, Gisela F; Scott, Cheryl; Raftery, Ann; Mase, Sundari; Watt, James P; Flood, Jennifer (Journal of clinical microbiology, 2010)
To assess the clinical impact of a molecular beacon (MB) assay that detects multidrug-resistant tuberculosis (MDR TB), we retrospectively reviewed records of 127 MDR TB patients with and without MB testing between 2004 and 2007. Use of the MB assay reduced the time to detection and treatment of MDR TB.